Clinical biochemistry an illustrated colour text - Gaw, Allan; Murphy, Michael J. (Michael Julian) 1963-; Srivastava, Rajeev; Cowan, Robert; O'Reilly, Denis St. J. (Illustrated colour text, 2013)
The clinical biochemistry laboratory -- The use of the laboratory -- The interpretation of results -- Point of care testing -- Reference intervals -- Fluid and electrolyte balance : Concepts and vocabulary -- Water and sodium balance -- Hyponatraemia : pathophysiology -- Hyponatraemia : assessment and management -- Hypernatraemia -- Hyperkalaemia -- Hypokalaemia -- Intravenous fluid therapy -- Investigation of renal function (1) -- Investigation of renal function (2) -- Urinalysis -- Proteinuria -- Acute renal failure -- Chronic renal failure -- Acid-base : concepts and vocabulary -- Metabolic acid-base disorders -- Respiratory and mixed acid-base disorders -- Oxygen transport -- Acid-base disorders : diagnosis and management -- Proteins and enzymes -- Immunoglobulins -- Myocardial infarction -- Liver function tests -- Jaundice -- Liver disease -- Glucose metabolism and diabetes mellitus -- Diagnosis and monitoring of diabetes mellitus -- Diabetic ketoacidosis -- Hypoglycaemia -- Calcium regulation and hypocalcaemia -- Hypercalcaemia -- Phosphate and magnesium -- Bone disease -- Osteoporosis -- Endocrine control -- Dynamic function tests -- Pituitary function -- Growth disorders and acromegaly -- Thyroid pathophysiology -- Hypothyroidism -- Hyperthyroidism -- Adrenocortical pathophysiology -- Hypofunction of the adrenal cortex -- Hyperfunction of the adrenal cortex -- Gonadal function -- Subfertility -- Nutritional assessment -- Nutritional support -- Parenteral nutrition -- The metabolic response to injury -- Gastrointestinal disorders -- Iron -- Zinc and copper -- Therapeutic drug monitoring -- Toxicology -- Metal poisoning -- Alcohol -- Coma -- Ascites and pleural fluid -- Cerebrospinal and other body fluids -- Lipoprotein metabolism -- Clinical disorders of lipid metabolism -- Hypertension -- Cancer and its consequences -- Tumour markers -- Multiple endocrine neoplasia -- Hyperuricaemia -- Myopathy -- Biochemistry in the elderly -- Fetal monitoring and prenatal diagnosis -- Pregnancy -- Antenatal screening -- Screening the newborn for disease -- Paediatric biochemistry -- Inborn errors of metabolism -- Selected inherited disorders -- Case history comments -- Web resources